Taurine Reduces tPA (Tissue-Type Plasminogen Activator)-Induced Hemorrhage and Microvascular Thrombosis After Embolic Stroke in Rat. Issue 7 (July 2018) - Jin, Rong; Xiao, Adam Y.; Liu, Shan; Wang, Min; Li, Guohong
Abstract : Background and Purpose—: Taurine (2-aminoethansulfolic amino acid) exerts neuroprotective actions in experimental stroke. Here, we investigated the effect of taurine in combination with delayed tPA (tissue-type plasminogen activator) on embolic stroke. Methods—: Rats subjected to embolic middle cerebral artery occlusion were treated with taurine (50 mg/kg) at 4 hours in combination with tPA (10 mg/kg) at 6 hours. Control groups consisted of ischemic rats treated with either taurine (50 mg/kg) or saline at 4 hours or tPA (10 mg/kg) alone at 2 or 6 hours after middle cerebral artery occlusion. Results—: We found that combination treatment with taurine and tPA robustly reduced infarct volume and neurological deficits 3 days after stroke, whereas treatment with taurine alone had a less-significant protective effect. tPA alone at 6 hours had no effects on infarct volume but instead induced intracerebral hemorrhage. The combination treatment with taurine prevented tPA-associated hemorrhage and reduced intravascular deposition of fibrin/fibrinogen and platelets in downstream microvessels and hence improved microvascular patency. These protective effects are associated with profound inhibition of CD147 (cluster of differentiation 147)-dependent MMP-9 (matrix metalloproteinase-9) pathway in ischemic brain endothelium by taurine. Notably, targeted inhibition of CD147 by intracerebroventricular injection of the rat CD147 siRNA profoundly inhibited ischemia-induced and tPA-enhanced MMP-9 activity in ischemic brain endothelium and blocked tPA-induced cerebral hemorrhage. Finally, the combination treatment with taurine and tPA improved long-term outcome at least 45 days after stroke compared with saline-treated group. Conclusions—: Our results suggest that taurine in combination with tPA may be a clinically feasible approach toward future attempts at combination stroke therapy. Abstract : Supplemental Digital Content is available in the text.